2021
DOI: 10.4049/jimmunol.2000756
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Peptides with Inadvertent Chemical Modifications Can Activate Potentially Autoreactive T Cells

Abstract: under the Erasmus Scheme. Beamtime was supported by proposals mx10462 and mx14843.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…It would be interesting to further investigate the consequences of the induction of these non-relevant T cells and to study whether they play a role in the observed increased lung pathology in mice vaccinated with MOD2. It has recently been suggested that chemical modification directly alters the immunogenicity of a peptide and could thereby lead to the activation of potentially autoreactive T cells via molecular mimicry of endogenous ligands 24 . Whether this also played a role in the increased lung pathology observed in MOD2-vaccinated mice remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to further investigate the consequences of the induction of these non-relevant T cells and to study whether they play a role in the observed increased lung pathology in mice vaccinated with MOD2. It has recently been suggested that chemical modification directly alters the immunogenicity of a peptide and could thereby lead to the activation of potentially autoreactive T cells via molecular mimicry of endogenous ligands 24 . Whether this also played a role in the increased lung pathology observed in MOD2-vaccinated mice remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We also surveyed other structures of nonameric peptides bound to HLA-A proteins and found several examples of peptides with large position 6 side chains positioned under the peptide backbone. The structure of the peptide IIGWMWIPV bound to HLA-A2 is a notable example: the conformation of the peptide backbone is nearly identical to that of the neoantigen, yet the tryptophan at position 6 is oriented down towards the base of the groove (43), resembling an intermediate for the under-peptide transition of the neoantigen (Extended Data Fig. 4F).…”
Section: The Flip In the Neoantigen Occurs With A High Energy Peptide...mentioning
confidence: 99%
“…It would be interesting to further investigate the consequences of the induction of these non-relevant T cells and to study whether they play a role in the observed increased lung pathology in mice vaccinated with MOD2. It has recently been suggested that chemical modification directly alters the immunogenicity of a peptide and could thereby lead to the activation of potentially autoreactive T cells via molecular mimicry of endogenous ligands [381]. Whether this also played a role in the increased lung pathology observed in MOD2-vaccinated mice remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%